English . - Tanggu Bore, Angela Yunita; Pradipta, Ngakan Bagus Danip (Jurnal Jaminan Kesehatan Nasional, 2024)
The community's preference for registering in the Regional Government-Subsidized Sumba segment rather than the informal workers segment may be influenced by several factors, such as income, family size, occupation, education, and the premium amount. This quantitative study uses a cross-sectional approach with a questionnaire and a minimum sample size of 415 participants selected through convenient sampling. The data were analyzed using binary logistic regression analysis. The results indicate that factors affecting participation in the Regional Government-Subsidized Sumba segment include education (OR = 0.53; p-value < 0.05), occupation (OR = 0.75; p-value < 0.05), family size (OR = 4.85; p-value < 0.05), and income (OR = 0.99; p-value < 0.05). However, the perception of premiums did not have a statistically significant effect (OR = 1.54; p-value > 0.05). This study's binary logistic regression model has a pseudo R² of 0.57, meaning that participation in the Regional Government-Subsidized Sumba segment is influenced by the independent variables by 57%. In comparison, 43% is influenced by other variables not examined in this study. Local governments must continue allocating health insurance funding each year. BPJS Kesehatan should also adopt a comprehensive approach and establish strong relationships with local governments to sustain Universal Health Coverage (UHC) in Sumba Regency